The association between CTSZ methylation in peripheral blood and breast cancer in Chinese women - Li, Jinyu; Zhou, Xiajie; Li, Lixi; Ji, Longtao; Li, Jiaqi; Qu, Yunhui; Wang, Zhi; Zhao, Yutong; Zhang, Jie; Liang, Feifei; Liu, Jingjing; Gu, Wanjian; et al. (Frontiers in Oncology, 2023)
Previous studies have shown that DNA methylation in peripheral blood may be associated with breast cancer (BC). To explore the association between the methylation level of the Cathepsin Z (CTSZ) gene in peripheral blood and BC, we conducted a case–control study in the Chinese population. Peripheral blood samples were collected from 567 BC cases, 635 healthy controls, and 303 benign breast disease (BBD) cases. DNA extraction and bisulfite-specific PCR amplification were performed for all samples. The methylation levels of seven sites of the CTSZ gene were quantitatively determined by Mass spectrometry. The odds ratios (ORs) of CpG sites were evaluated for BC risk using per 10% reduction and quartiles analyses by logistic regression. Our analysis showed that five out of the seven CpG sites exhibited significant associations with hypomethylation of CTSZ and BC, compared to healthy controls. The highest OR was for Q2 of CTSZ_CpG_1 (OR: 1.62, P=0.006), particularly for early-stage breast cancer in the case of per 10% reduction of CTSZ_CpG_1 (OR: 1.20, P=0.003). We also found that per 10% reduction of CTSZ_CpG_5 (OR: 1.39, P=0.004) and CTSZ_CpG_7,8 (OR: 1.35, P=0.005) were associated with increased BC risk. Our study also revealed that four out of seven CpG sites were linked to increased BC risk in women under 50 years of age, compared to healthy controls. The highest OR was for per 10% reduction of CTSZ_CpG_1 (OR: 1.47, P<0.001). Additionally, we found that BC exhibited lower methylation levels than BBD at CTSZ_CpG_4 (OR for Q1: 2.18, P<0.001) and CTSZ_CpG_7,8 (OR for Q1: 2.01, P=0.001). Furthermore, we observed a correlation between methylation levels and tumor stage, ER, and HER2 status in BC patients. Overall, our findings suggest that altered CTSZ methylation levels in peripheral blood may be associated with breast cancer, particularly in young women, and may serve as a potential biomarker for early-stage BC